2014
DOI: 10.1016/j.freeradbiomed.2013.10.811
|View full text |Cite
|
Sign up to set email alerts
|

Aldose reductase regulates miR-200a-3p/141-3p to coordinate Keap1–Nrf2, Tgfβ1/2, and Zeb1/2 signaling in renal mesangial cells and the renal cortex of diabetic mice

Abstract: Aberrant regulation in oxidative stress, fibrogenesis, and the epithelial-mesenchymal transition (EMT) in renal cells under hyperglycemic conditions contributes significantly to the onset and progression of diabetic nephropathy. The mechanisms underlying these hyperglycemia-induced dysregulations, however, have not been clearly elucidated. Herein, we report that aldose reductase is capable of regulating the expression of miR-200a-3p/141-3p negatively in renal mesangial cells. MiR-200a-3p/141-3p, in turn, act t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 48 publications
2
78
0
6
Order By: Relevance
“…Therefore, we hypothesized that HULC might promote angiogenesis as related to changes in ZEB1 and miR-200a-3p. It has been reported that ZEB1 is a target of miR-200a-3p via a luciferase reporter [42]. Notably, the EMT activators transforming growth factor beta2 and ZEB1 are the predominant targets downregulated by miR-200c.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we hypothesized that HULC might promote angiogenesis as related to changes in ZEB1 and miR-200a-3p. It has been reported that ZEB1 is a target of miR-200a-3p via a luciferase reporter [42]. Notably, the EMT activators transforming growth factor beta2 and ZEB1 are the predominant targets downregulated by miR-200c.…”
Section: Discussionmentioning
confidence: 99%
“…В эксперименте у мышей с СД было убедительно показано, что альдозоредуктаза (фермент сорбитолового пути утилизации глюкозы, содержа-ние которого увеличено при СД) снижает экспрессию miR-200а-3р и miR-141-3р и регулирует оксидативный стресс, воздействуя на ряд сигнальных путей (TGF-β1/ TGF-β2 и Zeb1/Zeb2 и др.) в мезангиальных клетках [49].…”
Section: сахарный диабет Diabetes Mellitusunclassified
“…The study established a reciprocal inhibiting effect between miR-200a/miR-141 and TGF- β 2. More recently, aldose reductase was found to elevate miR-200a-3p and miR-141 so as to coordinate kelch-like ECH-associated protein 1/NFE2-related factor 2, attenuating TGF- β 1/2 signaling in both renal cortex of STZ-induced mice and MMCs [55]. …”
Section: Downregulated Mirnas In Dnmentioning
confidence: 99%
“…Isoflavone and 3,3′-diindolylmethane (DIM) restored the expression of let7-b and led to the reversal of epithelial-to-mesenchymal transition in gemcitabine-resistant pancreatic cancer cells [104]. Because of the renal-protective role of miR-200a [54, 105] and let7-b [68], CDF, isoflavone, and DIM might prevent DN through regulating these two miRNAs.…”
Section: Therapeutic Speculation Of Mirnas In Dnmentioning
confidence: 99%